La rotation et les stratégies collectives de préservation de la santé développées par des opérateurs d’une usine de boissons - Raoni Rocha; François Daniellou; Adélaïde Nascimento (Activités)
This article aims to describe the regulation strategies developed by the employees of a beverage factory in order to respond to the constraints of an extremely restrictive production organization. These strategies are grounded in self-help and mutual cooperation. Using a qualitative methodology based on confrontation techniques, we observe that production operators on one of the production lines in this factory have only themselves to rely on to cope with the constraints of work: they organize themselves so as to ensure productivity and to safeguard their health. In this context, a complex system of strategies is developed, based on a sense of mutual cooperation and collective protection, to try to minimize fatigue and heavy work over the course of the workday.